Cathepsin D plays a role in endothelial–pericyte interactions during alteration of the blood–retinal barrier in diabetic retinopathy. Issue 5 (20th December 2017) - Monickaraj, Finny; McGuire, Paul; Das, Arup
Abstract : Inflammation plays an important role in the pathogenesis of diabetic retinopathy. We have previously demonstrated the effect of cathepsin D (CD) on the mechanical disruption of retinal endothelial cell junctions and increased vasopermeability, as well as increased levels of CD in retinas of diabetic mice. Here, we have also examined the effect of CD on endothelial‐pericyte interactions, as well as the effect of dipeptidyl peptidase‐4 (DPP4) inhibitor on CD in endothelial‐pericyte interactions in vitro and in vivo. Cocultured cells that were treated with proCD demonstrated a significant decrease in the expression of platelet‐derived growth factor receptor‐β, a tyrosine kinase receptor that is required for pericyte cell survival; N‐cadherin, the key adherens junction protein between endothelium and pericytes; and increases in the vessel destabilizing agent, angiopoietin‐2. The effect was reversed in cells that were treated with DPP4 inhibitor along with pro‐CD. With pro‐CD treatment, there was a significant increase in the phosphorylation of the downstream signaling protein, PKC‐α, and Ca 2+ /calmodulin‐dependent protein kinase II in endothelial cells and pericytes, which disrupts adherens junction structure and function, and this was significantly reduced with DPP4 inhibitor treatment. Increased CD levels, vasopermeability, and alteration in junctional‐related proteins were observed in the retinas of diabetic rats, which were significantly changed with DPP4 inhibitor treatment. Thus, DPP4 inhibitors may be used as potential adjuvant therapeutic agents to treat increased vascular leakage observed in patients with diabetic macular edema.—Monickaraj, F., McGuire, P., Das, A. Cathepsin D plays a role in endothelial‐pericyte interactions during alteration of the blood‐retinal barrier in diabetic retinopathy. FASEB J. 32, 2539–2548 (2018). www.fasebj.org